The Necessity to Shift to a Cultural Approach in Teaching Translation - KERRIS , Ismahane; BELOUAHEM, Riad (Journal of Human Sciences, 2023)
The present paper tries to investigate the necessity of including culture within the translation course syllabus at the Department of English (Universitè des Frères Mentouri Constantine 1). It attempts to show that teaching translation cannot be successful without relating it to culture. It tries, also, to determine the importance of teaching culture, first, in the foreign language classroom and second, within the translation course syllabus. Our study is based on a teachers’ questionnaire aiming at having some insights about the teacher’s and the student’s awareness of the concept of culture; in addition to their opinion about the importance of implementing culture within the translation course. The study validates the importance of implementing culture in both teaching and designing translation syllabi.